A Proposal for an Ultrasound/Sound Holographic Microscope Using Entangled Mobile Phone Inductors - Fioranelli, Massimo; Beesham, Aroonkumar; Sepehri, Alireza (Ultrasound International Open, 2022)
In this study we propose a model for building a holographic ultrasound microscope. In this model two mobile phones are first connected by waves and techniques like the WhatsApp waves. If the mobile phones are close to each other, their inductors and speakers become entangled, they exchange electromagnetic and sound waves, and they vibrate many times with each other. Objects placed between two mobile phones change the sound waves and electromagnetic waves and appear as holographic images within the inductors and also on the plastic of the speakers. To see these images, a hologram machine is built from a room of plastic, one or two magnets, iron particles, and sound producers. Holographic waves change the magnetic field within the hologram machine and move the plastic and iron particles. These objects take the shape of waves and produce holographic images. To see microbes, one can send a weak current to a container of microbes and then connect it to an amplifier. The weak current takes the shape of the microbes and is amplified by one strong amplifier. Then this current goes to the mobile phone and sound card and, after passing some stages, is sent to the second mobile phone. In the second mobile phone, the sound wave is amplified by speakers and transmitted to the hologram machine. Consequently, particles within this machine move and produce big holographic images of the microbes.
Keywords: ultrasound; methods & techniques; holography; microscope